PENGARUH TAYANGAN KARTUN NUSSA DAN RARRA TERHADAP AKHLAK ISLAMI SISWA KELAS 2 SD - Zulfitria Zulfitria; Chairusyifa Chairusyifa (Universitas Muhammadiyah Tangerang, 2022)
The background of this research is the development of technology and information in Indonesia so that there are many interesting cartoons to watch. So, in this study, the aim was to examine the Nussa and Rarra cartoons on Islamic morals for grade 2 elementary school students. The media used in this study were 8x Nussa and Rarra cartoon videos in order to see the effect of the cartoon. This research uses a pre-experimental design one shot case study research method. The data collection used in this research is in the form of an instrument validity test to test the truth of the hypothesis. The results of this study indicate that there is a significant effect of the Nussa and Rarra cartoons on the Islamic character of grade 2 elementary school students. This is evident from the results of the calculation showing the t- test value of 0.000 > 0.005, it can be concluded that there is an effect of Nussa and Rarra cartoons on Islamic morality in grade 2 elementary school students. The results of this study are expected to be useful for related parties who can be useful such as students, teachers, schools, parents, and further researchers.